2010
DOI: 10.4236/ijcm.2010.11006
|View full text |Cite
|
Sign up to set email alerts
|

NonOperative Management of Blunt Solid Abdominal Organ Injury in Calabar, Nigeria

Abstract: Background: Over the past several years, nonoperative management has been increasingly recommended for the care of selected blunt abdominal trauma patients with solid organ injuries. Objective: To evaluate the pattern and outcome of blunt abdominal trauma using haemodynamic stability and ultrasonography in the selection of patients for nonoperative management in a facility without computed tomogram. Methods: Patients admitted with blunt abdominal trauma between February 2005 and January 2010 were prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Isolated splenic injury that got converted was 36.8 is increased to 47.8% when combined injuries were included. 10 Present study shows CECT abdomen and grading of injury has important role in non-operative management of blunt injury abdomen. Up to grade 3 injury, nonoperative management have higher success rates and higher the grade higher is the chance of conversion to operative management.…”
Section: Discussionmentioning
confidence: 73%
“…Isolated splenic injury that got converted was 36.8 is increased to 47.8% when combined injuries were included. 10 Present study shows CECT abdomen and grading of injury has important role in non-operative management of blunt injury abdomen. Up to grade 3 injury, nonoperative management have higher success rates and higher the grade higher is the chance of conversion to operative management.…”
Section: Discussionmentioning
confidence: 73%
“…Maurice A et al [11] in Nigeria also observed Road traffic accidents were the commonest cause of abdominal injury. Tiwari C et al [8] in a study from Mumbai, India also observed that the Road traffic accident was the most common mode of injury seen in 14 patients (58.33%), followed by fall from height in 7 patients (29.16%) and these findings were similar to the findings of the present study.…”
Section: Discussionmentioning
confidence: 94%
“…The spleen was the commonest organ affected in blunt abdominal injury as has also been recorded elsewhere. [18,19] The neurosurgery unit also had high number of patients who sustained severe head injury from motorcycle accident. In our country, from a recent review, many motorcycle riders and their passengers do not wear helmets.…”
Section: Discussionmentioning
confidence: 99%